Mahan excitons in room-temperature methylammonium lead bromide perovskites - Tania Palmieri (Nature Portfolio, 2020)
The Mahan exciton, exotic quasiparticle predicted in 1967, had never been found in room temperature semiconductors. With ultrafast optics and many-body theory, Palmieri et al. show that methylammonium lead bromide perovskites are ideal platforms to unveil Mahan exciton physics at room temperature.